Pills, Pills, and More Pills: A Pill Box Exercise to Teach Barriers to Medication Adherence and Solutions - Kathryn Denson; Jessica Kuester (Association of American Medical Colleges, 2015)
Abstract Introduction Teaching about polypharmacy and medication reduction in a didactic lecture format is challenging. A variety of educational efforts relating to medication adherence have been used, and described, in the literature. There have been a few experiential training approaches using mock prescription exercises which have been described. This curriculum, an interactive, hands-on polypharmacy experience paired with group reflection, improves learner knowledge of medication adherence barriers and solutions, resulting in decreased number and dosing frequency of medications of elderly patients. Methods At the first session, each learner starts by filling out a presurvey. Each learner is then given a pill box to fill with medications (actually, various candies) according to the medication list of an actual geriatric patient. The learners fill the boxes, and a faculty member facilitates a discussion about challenges to filling a box (e.g., dementia, arthritis, visual loss, neuropathy). Learners are instructed to take the medications as prescribed for one week. At the second session, one week later, learners report back to the group and describe their experience. The faculty member then facilitates a discussion about barriers and solutions that could be used to aid adherence. Learners end the exercise by taking a postsurvey. Results The exercise has been used with a variety of learner levels: M1 (N = 30), M3, M4 (N = 25), and PGY 1-4 (N = 23). This exercise has generally been used in small groups of six learners during their geriatrics rotation but was also used in our Senior Mentor Program with a group size of 30. Initial data (N = 78) showed an increased understanding of adherence barriers (3.5 to 4.9) and solutions (3.0 to 4.8), as well as increased patient medication education (2.6 to 4.0) and increased medication discontinuance/dosing changes (3.0 to 4.3), on a scale of 1-6, with 6 as highest. Results varied by learner level, with most medication dose changes at the resident level. Discussion This educational resource has some limitations. Given that it is a simulation, it cannot completely replicate the experience of being asked to take multiple medications multiple times each day. This resource is not designed to be a "true replication" of the pill taking experience as much as an experience to sensitize the learners to the true difficulty of medication adherence and to help that understanding "stick" in a way that will hopefully change prescribing practice and increase patient education.